How to assess the systemic risk buffer for banks - Sverre Mæhlum; Magdalena D. Riiser (Norges Bank, 2019)
Since 2013, Norwegian banks have been required to hold a systemic risk buffer (SyRB) of 3 percent. The reason for the buffer is to address structural vulnerabilities in the economy and the financial system. The Ministry of Finance has proposed an increase in the buffer requirement to 4.5 percent. A framework for the use of the buffer has not been established in Norway or the EU. The countries that have introduced the buffer have used different indicators and cited different reasons. In this paper, we assess indicators and a possible framework for the systemic risk buffer in Norway. We find that a number of structural features of the banking sector indicate that systemic risk is high in Norway, and there are many indications that structural systemic risks have risen in recent years.
hdl:11250/2653109
Keywords: 330; Systemic risk buffer; structural systemic risk; indicators